The History of Accounting - One of the Oldest Economic Disciplines - Staszel, Anna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
It is possible to find signs of accounting as far back as prehistoric times, when it constituted the essence of the then contemporary economic thought and solved problems involved in joint labour. This publication presents the history of accounting from the first bookkeeping account through Luca Pacioli's work that is so crucial to the history of accounting and, finally, the evolution of the bill of charges that was created for the needs of the first capitalists. Research on the system of accounting is presented, as are deceitful financial reporting and the establishment of the profession of Chartered Accountants. The history of accounting shows that it is one of the oldest disciplines of economic studies and, most importantly, the foundations of accounting have stood the test of time. The structure of a bookkeeping account with a Dt and Ct page has remained unchanged for over five thousand years.